Recognition of G-quadruplexes in microRNA precursors by nucleolin and its implications in cancer - Santos, Tiago André Afonso dos (2022)
Cancer is among the most frequent pathologies, and it is responsible for high mortality rates, which tend to increase year by year. In order to restore the well-being of citizens, numerous efforts have been performed to develop new diagnostic and therapeutic approaches. However, ensuring the effectiveness of these new approaches is a challenging task. Indeed, it is necessary to study the mechanisms and molecular interactions during cancer development. Several molecular mechanisms related to cancer development have been studied in the past decades. Their study encouraged the identification of new nucleic acid structures, which can adopt alternative secondary conformations. Among these structures are G-quadruplexes (G4), three-dimensional structures formed in the genome or transcriptome of regions rich in guanines. G4 DNAs are located in key regions of the genome, including the ends of telomeres and oncogenic promoters, and have received considerable attention from the scientific community in the past two decades. On the other hand, the G4 RNAs found in non-coding regions have recently received this interest due to their importance in controlling multiple biological processes. In this way, the intermediates of microRNA biogenesis (miRNAs) that can adopt a G4 structure have been more intensely studied, focusing on microRNA precursors (pre-miRNAs). The development and/or study of small molecules (G4 ligands, molecular weight < 500 Da) with the ability to bind and stabilize/destabilize G4 structures could strongly contribute to the modulation of miRNA biogenesis. G4 ligands have shown high potential to be applied to the diagnosis and therapy of several pathologies such as neurodegenerative diseases, cancer, and viral infections. Acridine orange derivatives have been demonstrated to bind and stabilize different DNA and RNA G4 structures. Besides small molecules that bind to G4 structures, there are other approaches to control the biogenesis of miRNAs, which are also attractive. Indeed, the process is essentially modulated by proteins, which reveals its potential to be modulated by interfering with those molecules. In this way, the most widely used approach aims to influence Dicer activity, a protein with enzymatic activity that cleaves pre-miRNAs into miRNAs. However, other equally relevant approaches could be explored. Nucleolin is a protein highly expressed in cancer cells. The protein is involved in several cellular processes, including tumorigenesis, angiogenesis, and extracellular signaling pathways. Nucleolin is mainly located in the nucleolus but can also be found in the nucleoplasm, cytoplasm, and cell surface. Recently, it has been described that nucleolin is involved in miRNA biogenesis through its interaction with the microprocessor complex. However, since has been described as a protein with a high affinity for parallel G4 structures, and in cancer cells performs the transport of several molecules between the cytoplasm and the nucleus, its action at this stage of biogenesis is a robust hypothesis. In this way, this thesis aims to deal with the interaction of the G4s adopted by pre-miRNA let 7e, 92b, and 149, with ligands and nucleolin. Indeed, the expression levels of these pre-miRNAs and miRNAs have been found dysregulated in several types of cancer. In addition, the potential biological applications of the recognition of these sequences by ligands and nucleolin were addressed. The formation of G4s in the sequences of the pre-miRNA let 7e, 92b, and 149 were evaluated under different experimental conditions (concentration, ionic strength, and temperature). In addition, the stabilizing/destabilizing effect of the ligands on the G4s was evaluated and they are dependent on the experimental conditions. For example, the ligand C8, depicts a modest impact in stabilizing the G4 of pre-miRNA let 7e, but stabilized the G4s of pre-miRNAs 92b and 149. Once we established the potential of G4 ligands to stabilize the G4s present in miRNAs, we evaluated the G4/nucleolin molecular interactions in the presence and absence of ligands. In the case of the G4 in pre-miRNA let 7e, the formation of the ternary complex G4/ligand/nucleolin was observed, except in the presence of the ligands PhenDC3 and TMPyP4, which seem to destabilize the G4 structure. Thus, these two ligands have the potential to control the miRNA biogenesis by increasing miRNA let 7e expression levels. The formation of the ternary complex was not affected by the presence of C8. In the studies performed with the G4 structure of pre-miRNA 92b, the acridine derivatives showed high potential to stabilize the structure, namely C8. Also, this ligand does not significantly affect the recognition of nucleolin by G4. Therefore, the G4/C8 complex was tested in a microfluidic device to sense nucleolin in plasma samples from prostate cancer patients. Finally, even known for its enormous relevance in several cancer-associated processes and mechanisms, the G4 sequence of pre-miRNA 149 has been less studied than those previously described. Furthermore, the G4 sequence overlaps almost entirely with the miRNA 149-3p, which presents an opportunity to act at different stages of miRNA 149 biogenesis. Considering this evidence, we aim to study in-depth the G4 sequence of pre-miRNA 149 in terms of its interaction with ligands and nucleolin. Furthermore, due to its high potential, the G4 structure was tested as a potential strategy to recognize and detect nucleolin 0n the surface of cancer cells. First, the formation of the G4 structure was confirmed by several biophysical techniques and revealed a G4 structure of high structural complexity. Then, the binding mode and interaction of different G4 ligands with the G4 structure were analyzed, and the results showed a high potential of the ligand C8 to stabilize the G4 structure. We also analyzed the complete sequence of pre-miRNA 149 and demonstrated its ability to detect nucleolin using a microfluidic system manufactured by INESC-MN. Finally, the interaction of G4 and the G4/C8 complex with nucleolin was also investigated and revealed a binding pocket in the 3D structure of nucleolin domains 1 and 2. Overall, these results revealed the biological potential of the G4 sequences in pre-miRNA let 7e, 92b, and 149. The structural regulation of G4 sequences present in pre-miRNAs can enable the development of applications for cancer diagnosis and therapy. Therefore, we anticipated that structural studies of the G4/nucleolin interaction would be available in the future, leading to the emergence of new ligands with inhibitory or enhancing effects on the interaction.